Peningkatan Literasi Akuntansi Syariah Pada Siswa SMK - Ervina, Deasy; Pertiwi, Dwi Ari; Agustina, Rachma; Ardiana, Meta (Dinamis: Jurnal Pengabdian Kepada Masyarakat, 2022)
The sharia accounting is not only required for university, but is needed also for senior high school, moreover SMK that opened sharia banking majors.SMK graduates are expected to be experts and able to work in sharia financial institute. Sharia accountancy education is needed to support professionals in carrying out sharia based economic transactions. Hopefully, students SMK become more aware and understand sharia accounting that previously don’t understand. The purpose of this activity to make SMK students accounting major can understand sharia accounting which will be their provision in competing in corporate world. Stage of the implementation get started by make proposal of PKM, then propose to LPPM, next contact schools that will be a place activities implementation and set schedule for implementing. After get day appropriate by their school activity and implementer lecturers, then the activity carried out.The goals set by this PKM is targeted to national journal.